Beyond the Pulp Vanguard: Bruce Andrews's Film Noir Series and the Dead-End of Escapist Experimentalism. Issue 3 (September 2021) - Guimarães, João Paulo
Abstract : Despite the fact that Bruce Andrews's interests cut across different aesthetic media, with concepts from music, dance and film many times determining the formal and conceptual contours of his compositions, scholars most often examine the latter as bona fide works of poetry. In this essay, we will attend to and flesh out the significance of Andrews's dialogue with the medium of cinema in two chronologically distant works: Film Noir (1978) and Swoon Noir (2007). I will contend that while Andrews uses the noir, in the first book, to attack the sensorially disabling nature of immersive art, in the second one, the famed pulp genre functions as a grand metaphor through which the poet addresses the ineffectiveness of intentionally non-immersive avant-garde works, like his own 1978 piece, to carry out a much-promised perceptual and ethical awakening. There is, perhaps, in Andrews's view, an escapist element, very much like that which colours most detective pulp fiction and cinema, to innovative works that purport to be forward-thinking and transformative but end up promoting a feel-good mood of powerless rapture and amazement. In this piece, we fully flesh out Andrews's critique of the vanguard's 'cinematic' ambitions and assess the alternative 'miniature' aesthetics he proposes. Only by drawing out and bringing its innovations into focus, Andrews claims, will the avant-garde be able to rescue the transformative modes of experience it reveals from their dilution in sublime-soaked pulp poetics.